CARDENIO’S VARIOUS FORTUNES (Journal of Contemporary Philology, 2022)
This paper revisits a presumably lost Jacobean play, The History of Cardenio, attributed to John Fletcher and William Shakespeare. This adaptation of Miguel de Cervantes’ story featured in the first part of Don Quixote has been the subject of many conjectures and hypotheses throughout the centuries, primarily because of Lewis Theobald’s 1728 Double Falsehood, which he claimed was the lost play in question. Following Stephen Greenblatt’s work on cultural poetics and cultural mobility – concerning issues of authorship, mobility of ideas and texts, the relationship between society and literature – we will first retrace the trajectory of Cervantes’ Don Quixote from Spain to England in the early XVII century and examine its reception among the writers of the time. We will then focus on several notices that an adaptation of a story featured in Don Quixote was performed in the English playhouses of the time, a play later attributed to Fletcher and Shakespeare, which was never published and was considered lost up until the XVIII century and the publication of Double Falsehood. Finally, we will give a brief critical analysis of the several texts in circulation, a notice of the most recent findings and conclusions on the Cardenio issue, and an account of the XXI century adaptations of the play around the world, a project carried by Stephen Greenblatt.
Keywords: cultural poetics; reception; adaptation; Shakespeare; Cervantes